The Role of knowledge workers in enhancing Crisis Management An Analytical study of the Opinions of Administrative leaders at the University of Fallujah - Ammar Hasan Faleeh Al-Jubouri,; Basem Faisal Abd Nayef, (Technium EconomiA, 2025)
The current research aims to demonstrate the extent of the strength of benefiting from knowledge workers in preparing for crisis management at the University of Fallujah, employing the descriptive analytical approach. To achieve the objectives of the research, the researchers designed a questionnaire as a tool for collecting information. The facilitated non-probability sample method was used, which allows data to be collected from the community in a comfortable manner. A sample of university leaders was chosen, represented by the colleges of the University of Fallujah, namely (Administration and Economics, Law, Veterinary Medicine, Islamic Sciences, Medicine, Applied Sciences and Education), which constitute (185) employees out of the total number of colleges at the University of Fallujah, the research reached several results, the most important of which is that there is a relationship of association and influence between knowledge workers and crisis management among its leaders, which is considered an effective means of success, development and progress at the University of Fallujah. The researchers presented a set of proposals that are consistent with these conclusions, the most important of which was the necessity of enhancing the role of knowledge workers in the university by integrating them into decision-making committees and developing Proactive strategies focusing on innovation and overcoming crises experienced by the University of Fallujah.